Issues of sustainable development in civil engineering in Portugal - Alfredo Soeiro (2008)
There are, in Portugal, nine universities with degree programs of civil engineering accredited by the Ordem dos Engenheiros (Engineering Professional Body). However, none of them present disciplines expressly dedicated to teach or to learn SD in the study plan. In the two last years of the five year study plan, generally in the fourth year of degree, most of the courses of civil engineering introduces SD in an implicit way. It is for instance associated to studies of town planning and of evaluation of environmental impacts. Of the nine degree programs of civil engineering analyzed, in the option of building construction, only two present disciplines that are optional and are directly associated with sustainable construction. Six present disciplines of evaluation of environmental impact and of town planning. The importance of SD in a degree program of civil engineering is unquestionable. Some of the issues like building maintenance and management represent a large impact on energy spending and on pollution of the atmosphere and of the earth. Another area of civil engineering that is important for SD is hydraulics and the water, river and sea management. A very important area is the cycle and recycle of construction materials with the creation of by-products that are one of the main sources of environment contamination. There are many other areas of civil engineering where SD is very important like transportation, planning and industrial construction. The adaptation of civil engineering disciplines of the SD principles and theories will prepare the future civil engineers to address their profession with SD as a major concern and beacon. The continuing education and professional development activities and courses will have a quicker impact on the transformation of the actions of the current civil engineers.